Continental land banks and land registers - O'Brien, Murrough (Statistical and Social Inquiry Society of Ireland, 1887)
The Statistical Society allowed me on a former occasion to give an account of a Swiss State Land Credit Bank, from the operations of which it seemed to me some useful lessons might be learned. The question of making loans with safety on small parcels of land in Ireland is a matter of vital importance in the reformation of our land system. A large amount of public money is being lent to Irish farmers on the security of their holdings, and still larger advances are in contemplation. The lending of these large sums without loss to the taxpayer, and with advantage to landlords and tenants, is supposed by some persons to be fraught with danger; it has not yet passed beyond the experimental stage. The various measures which have been passed since 1870 with this object have been characterized by vacillation, timidity, obscurity, and want of any definite principle. No sooner have they been passed, than demands are made that they should be amended, and no settled principles seem to have been arrived at as to the amount and terms of loans, or the means by which they are to be secured. Numerous continental land banks all work on the same general lines; the business of safe lending on land is just as well understood, its principles are as settled, as those of ordinary banking in this country.
Read, Tuesday, 7th June, 1887
Keywords: Land banks; Mortgages; Banking in France; Credit Foncier; 314.15